Foreign country priorities in the internationalization process: A measure and an exploratory test on British firms - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 2001)
After a critical analysis of the psychic distance aspect of the Uppsala model of internationalization and empirical studies to test it, this paper proposes a measure to enable comparison between target foreign countries in the priority given them in the internationalization process. An International Priority Index is developed for each target country, and used as the dependent variable in a model to analyze the effects of the independent variables of size of market, affluence of market, geographical distance and cultural distance on foreign country priority choice of home country firms. The measure and the model are given a first test on data obtained from a longitudinal study of the ordering of foreign market entry of 19 British firms. In this study, affluence of market is shown to have more importance than size of market, and geographical distance of country to have greater impact than cultural distance in the choice of ordering of entry.